A short-term, post-Lomagundi positive C isotope excursion at C. 2.03 Ga recorded by the Wooly Dolomite, Western Australia. - Bekker, A.; Krapez, Bryan; Müller, S.; Karhu, J. (Geological Society Publishing House, 2016)
It is generally accepted that carbon isotope variations in seawater were muted between c. 2.06 Ga, after the end of the Lomagundi carbon isotope excursion (LCIE), and c. 1.3 Ga. Evidence is presented here that c. 30 myr after the end of the LCIE, the biogeochemical cycle of carbon experienced a short-term (c. 2 myr), high-amplitude (up to +8.4‰ V-PDB) perturbation, recorded in the Horseshoe rift basin, Western Australia. The basin was initiated at c. 2.03 Ga with deposition of fluvial and shallow-marine sandstones, followed by the eruption of flood basalt, and culminated with the deposition of platform carbonates, and accompanying volcaniclastic and siliciclastic sediments (Wooly Dolomite). The Horseshoe rift basin during deposition of the Wooly Dolomite was fault-compartmentalized but connected to an ocean. Six depositional sequences make up the Wooly Dolomite. Sequence 1 records establishment of a carbonate platform conformably on basalt and coevally with volcaniclastic sedimentation. All other sequences have dominant carbonate-platform deposits and are unconformity-bounded. Sequence 3 contains a c. 57 m thick section with13C-enriched carbonates bracketed between carbonates with close to 0‰ carbon isotope values. Further high-resolution chemostratigraphic studies may reveal a more complex pattern of carbon isotope variations during the ‘boring billion years’, but without precise geochronology similar short-term carbon isotope excursions in carbonate successions could be incorrectly correlated to the LCIE.